2023
DOI: 10.2105/ajph.2022.307153
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Interventions to Prevent Dating and Relationship Violence and Gender-Based Violence: Systematic Review and Network Meta-Analysis

Abstract: Background. Schools are sites of dating and relationship violence (DRV) and of gender-based violence (GBV) victimization and perpetration. School-based interventions can reach a broad range of students, targeting both individual and group processes that may underpin DRV and GBV. Considering DRV and GBV jointly is important because of their shared etiologies. Comparing the effectiveness of interventions using network meta-analysis (NMA) can support decision-making on optimal resource use. Objectives. To evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…Full results are provided elsewhere. [6][7][8][9] Searches identified 40,160 unique records, of which 793 were screened in full text. Of these, 68 outcome evaluations and 137 process evaluations were eligible for inclusion.…”
Section: Overview Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Full results are provided elsewhere. [6][7][8][9] Searches identified 40,160 unique records, of which 793 were screened in full text. Of these, 68 outcome evaluations and 137 process evaluations were eligible for inclusion.…”
Section: Overview Of Resultsmentioning
confidence: 99%
“…All these analyses are reported in detail elsewhere. 6,7 Drawing on inductive syntheses, we found that there were overall interventions effects on long-term (1 year or above) but not short-term (less than 1 year) DRV perpetration and victimisation. Forest plots and pooled estimates are reported elsewhere.…”
Section: Synthesising Outcome Evaluationsmentioning
confidence: 94%
See 3 more Smart Citations